UTILIZATION OF OPTIMAL MEDICAL PHARMACOTHERAPY IN PATIENTS WITH TYPE 2 DIABETES AND ATHEROSCLEROTIC CARDIOVASCULAR DISEASE: INSIGHTS FROM AN INTEGRATED HEALTHCARE SYSTEM - Izza Shahid, MBBS; Budhaditya Bose, MS; Eleonora Avenatti, MD; Safi U. Khan, MD MHS; Mohamad B. Taha, MD; Khurram Nasir, MD MPH MSc (Elsevier, 2023)
Therapeutic Area: Pharmacologic Therapy Background: Patients with atherosclerotic cardiovascular disease (ASCVD) and concurrent type 2 diabetes mellitus (T2DM) are at an increased risk for adverse cardiovascular outcomes, and derive significant mortality benefit from secondary prevention therapies. Despite this, utilization of evidence-based optimal medical therapy (OMT) remains suboptimal in this cohort. Therefore, we sought to determine contemporary patterns in utilization of OMT for secondary prevention in patients with ASCVD and T2DM. Methods: Houston Methodist Cardiovascular Disease Learning Health System Registry, an EMR-linked registry was queried to obtain data of adult population between 2016-2022. All patients with established ASCVD (i.e. coronary artery disease, peripheral artery disease and/or stroke) and T2DM diagnosis based on ICD-10 CM codes were included. OMT was defined as any patient utilizing high-intensity statin, antithrombotic (antiplatelet or anticoagulant), ACEi and/or ARB [angiotensin converting enzyme inhibitor and/or angiotensin II receptor blocker], and SGLT2 inhibitor and/or GLP1 RA [sodium-glucose cotransporter-2 and/or glucagon-like peptide 1 receptor agonist]. Patients with glomerular filtration rate<30ml/min/1.73m2 were excluded. Results: A total of 31,611 patients with ASCVD and T2DM were included in this analysis (mean age 71.3±10.5; 57.5% men). Of these, 56.7% utilized high-intensity statin, 68.9% used ACEi and/or ARB, 63.8% received antithrombotic therapy while SGLT2i and/or GLP-1 were used in 33.0% patients. Overall, 3,553 (11.2%) patients ever received comprehensive OMT with a modest increase observed overtime (2.3% in 2016 vs 6.0% in 2022; p<0.01). An increasing trend of high-intensity statin (30.3% vs 41.8%; p<0.01) and SGLT2i and/or GLP1 RA (12% vs 26%; p<0.01) use were observed overtime. Conversely, utilization of ACEi and/or ARB decreased overtime (51% vs 43%; p<0.01). Compared with the overall cohort, patients utilizing comprehensive OMT were significantly less likely to be women (33.1% vs 42.5%; p<0.01), ≥65 years of age (68.4% vs 77.2%; p<0.01) and of Asian descent (6.0% vs 7.0%; p<0.01). Conclusions: In this large contemporary community-based cohort, utilization of evidence-based OMT remains suboptimal for secondary prevention in patients with ASCVD and T2DM, with minimal improvement overtime. Despite proven cardiovascular benefit, utilization of ACEi and/or ARB decreased overtime. However, encouraging trends were observed in the use of high-intensity statins and novel SGLT2i and/or GLP1 RA. Concerted efforts are required to improve implementation of guideline-recommended therapies in this high-risk cohort.